An Analysis of Actantial Model in the Avatar: The Last Airbender (2024) TV Series - Arhim, Alya Natasha Zahrani; Max, Jonathan Irene Sartika Dewi (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2025)
This research aims to reveal the actantial scheme and actantial roles of the major characters in the first season of Avatar: The Last Airbender (2024) TV series. Using the actantial model theory developed by A. J. Greimas and applying a structuralist approach, the researchers analyze the characters’ actions. Furthermore, the researchers use qualitative methods to collect and analyze relevant data. Based on the results of the analysis, the researchers identify three schemes, which are considered complete as they contain all the key elements: a subject, object, sender, receiver, helper, and opponent. The researchers also provide an analysis of the characters’ characterization to reveal their actantial roles in each scheme. The types of characterization that appear the most are characterization through dialogue between characters and the external actions of characters.